Envisioning Inclusive Justice: Optimizing the Role of Advocates as Officium Nobile in the Provision of Legal Aid - Simanjuntak, Timoty Ezra; Situmeang, Jokki Obi Mesa; Riyadi, Aldo Prasetyo; Sipayung, Nico Hermawan (Dinasti Research, 2025)
This study examines the role of advocates as officium nobile in realizing inclusive justice through optimized legal aid. It uses a juridical-normative approach with a conceptual and legislative focus, relying on secondary data and qualitative analysis. The study finds that advocates, as officium nobile, have a moral and ethical duty to provide legal aid to those in need, particularly the economically disadvantaged or legally uninformed. Advocates can optimize their role by collaborating with local government officials at the Village and District levels for pro bono activities. The study recommends that advocates with at least 10 years of practice establish and manage a Legal Aid Institution, either independently or with others, to address legal aid challenges in Indonesia. Additionally, the author proposes an alternative scheme where advocates contribute donations, regulated in amount and time, to support the operations of Legal Aid Institutions.